Forming Catholic communities: Irish, Scots, and English college networks in Europe, 1568-1918 - Chambers, Liam; O'Connor, Thomas (Catholic Christendom, 1300-1700, 2018)
Irish collegians in Spanish service (1560-1803) / Thomas O'Connor -- Seraphic sparks : the Irish Franciscan and Capuchin colleges on the continent / Micheal Mac Craith -- Pietas Austriaca and "dispensers of royal authority" : the early Irish colleges and Habsburg cultural strategies / Declan M. Downey -- "Bullworks against the furie of heresie" : identity, education, and mission in the English Jesuit College of St Omers / Jan Graffius -- The English Benedictines in eighteenth-century Lorraine / Frederic Richard-Maupillier -- The Spanish court, ecclesiastical patronage, and the Irish College of Santiago de Compostela (1611-17) / Ciaran O'Scea -- The early failures of the Irish College Rome, 1628-78 / Matteo Binasco -- Financial mismanagement at the Irish College, 1772-98 1/ Christopher Korten -- English recusant controversy in Spanish print culture : dissemination, popularisation, fictionalisation / Ana Saez-Hidalgo -- Creating an Irish identity : print, culture, and the Irish Franciscans of Louvain / Marc Caball -- The "British establishments", the Irish College in Paris and Restoration France, 1814-30 / Liam Chambers -- The trouble with France : making Scots priests in France, 1818-78 / Iida Saarinen -- The transformation of the Irish College, Paris : war, education, and administration, 1870-1918 / Justin Dolan Stover